Enhancing video transmission in MANETs utilizing multiple interfaces and multiple channels per node - Christos Bouras; Apostolos Gkamas; Vaggelis Kapoulas; Dimitra Politaki; Enea Tsanai (5th International Conference on Ad Hoc Networks, Barcelona, Spain, 2013)
Mobile Ad hoc NETworks (MANETs) are becoming more essential to wireless communications due to growing popularity of mobile devices. MANETs are also essential in Emergency Response situation where network information flow between deployed units is vital. In such cases voice and video transmission is essential to form a global view of the situation and decide on action. However, MANETs do not seem to effectively support multimedia applications and especially video transmission. In this work we propose a simple and efficient channel selection mechanism for enhancing Video Transmission in MANETS that have nodes with multiple interfaces, and can utilize multiple channels at the same time. The mechanism is implemented and tested in the ns-2 network simulator. Simulation results indicate that the mechanism improves the networks capacity for video transmission and reduces the video streams? packet delay.